Exposure to Communication Media by the Poultry Farmers in Receiving Information (South Asian Journal of Agriculture, 2022)
Innovations are being diffused to the farmers’ community through various communication media. However, which communication media is favorably utilized by the poultry farmers are not yet identified. The purpose of the study was to determine the extent of the exposure to communication media by the poultry farmers in receiving information. Attempts were also made to explore the relationship between the selected characteristics of the poultry farmers and their extent of exposure to communication media. Data were collected from randomly selected 60 poultry farmers of three villages of Jalma union under Batiaghata Upazilla of Khulna district, Bangladesh. Major percentage (58.3%) of the respondents showed medium exposure to individual media, however, most of them are little exposed to group and mass media (85% and 75% respectively). Irrespective of the type of media, lower level of exposure was expressed by most of the respondents (90%). Among the 16 communication media under three board categories, the respondents were highly exposed to neighbor and less exposed to radio. The personal characteristics of the poultry farmers as level of education, farm size and participation in training showed a positive significant relationship with their extent of use of communication media. Individual media (e.g. Information from neighbor) was most favorably utilized by the poultry farmers for receiving information regarding farming.South Asian J. Agric., 8(1&2): 6-12